Enhancement the larvicidal activity of nanostructure copper oxide against Culex pipiens mosquito by yttrium replacement based on crystallite size reduction and topographic surface nature. (10th November 2021) - Mostafa, Wageha A; Abdel-Raoof, Ahmed M; Attala, Khaled; Elgazzar, Elsayed
Abstract: The current work aims to improve the metal oxide characteristics for mosquito control. Un-doped and Y-doped CuO have been synthesized by simple chemical route. Structural, composition, and morphological properties were characterized by XRD, Raman spectra, EDX, SEM, and TEM techniques. The obtained results revealed that CuO was strongly affected by Y 3+ support, in which the crystallite size decreased, and the surface area increased. Larvicidal performance was assessed against Culex pipiens suggesting that the nanocomposite CuO/Y of higher efficiency (LC50  = 7.67 mg /l, R 2  = 0.977) compared with pure CuO. Light microscopy and SEM images exhibited larvae malformations owing to using the fabricated nanomaterials.